GUGATAN BALIK KORPORASI TERHADAP SAKSI AHLI LINGKUNGAN: ANALISIS SLAPP DAN GOOD CORPORATE GOVERNANCE - Ananda, Syifa Kaffah; Nugroho, Wahyu; Fahririn (Jurnal Yuridis, 2025)
The practice of corporate counterclaims against environmental expert witnesses in forest fire cases shows symptoms of legal abuse in the form of Strategic Lawsuit Against Public Participation (SLAPP). This study analyzes the case of PT Jatim Jaya Perkasa against Prof. Bambang Hero Saharjo in the perspective of SLAPP in Indonesia and examines the role of Good Corporate Governance (GCG) principles in limiting deviant corporate actions. This research uses normative juridical method with statutory approach and case approach. The data is analyzed descriptively qualitatively. The results show that the lawsuit contains elements of intimidation against scientific and public participation in environmental law enforcement. Although Article 66 of the PPLH Law, Permen LHK No. 10 of 2024, and Perma No. 1 of 2023 have provided a basis for legal protection for environmental fighters, including expert witnesses, the implementation of the three regulations is still weak and has not become an effective guideline at the practical level. Therefore, it is necessary to strengthen the implementation of regulations through active supervision and internalization of GCG values by corporations so that the law is not used as a tool of repression against public participation.